2016
DOI: 10.5271/sjweh.3557
|View full text |Cite
|
Sign up to set email alerts
|

Methodological and conceptual issues regarding occupational psychosocial coronary heart disease epidemiology

Abstract: OverviewPsychosocial occupational epidemiology has mainly focused on the demand-control and, to a much lesser extent, the effort-reward-imbalance (ERI) models. These models and the strong focus on them raise some conceptual and methodological issues we will address in the following letter.The conceptual issues include the empirical confirmation of the assumptions of these models, the extent to which the focus on the demand-control and ERI models is warranted, and whether the sub-dimensions of the scales in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 22 publications
0
33
0
3
Order By: Relevance
“…A further issue with meta‐analyses for work stress is that concepts, such as job strain, effort‐reward imbalance, and organizational injustice, are typically characterized in a median or quartile split across the population investigated. As Burr et al outlined in their Letter to the Editor, whether certain individuals are identified as having job strain, and therefore have work stress, depends on who else is in the sample . This is problematic when work demand, control, and other work environment related characteristics vary between jobs and across countries.…”
Section: Work Stress and Chdmentioning
confidence: 99%
See 1 more Smart Citation
“…A further issue with meta‐analyses for work stress is that concepts, such as job strain, effort‐reward imbalance, and organizational injustice, are typically characterized in a median or quartile split across the population investigated. As Burr et al outlined in their Letter to the Editor, whether certain individuals are identified as having job strain, and therefore have work stress, depends on who else is in the sample . This is problematic when work demand, control, and other work environment related characteristics vary between jobs and across countries.…”
Section: Work Stress and Chdmentioning
confidence: 99%
“…As Burr et al outlined in their Letter to the Editor, whether certain individuals are identified as having job strain, and therefore have work stress, depends on who else is in the sample. 53 This is problematic when work demand, control, and other work environment related characteristics vary between jobs and across countries. If the prevalence of job strain varies between populations and is inherently dependent on the distribution of demands and control within that population, combining data from different populations as part of a metaanalysis can become challenging.…”
Section: Rewards -Salary -Esteem -Security -Promotionmentioning
confidence: 99%
“…A recent multi‐cohort study reported that the combination of job strain and ERI was associated with a 40% higher risk of coronary heart disease, although the excess risk of each stressor separately was only 16% 22 . However, the real psychosocial work environment has a variety of possible psychosocial factors; some of these were considered in the models and others were not 20 . Thus, co‐exposure to a variety of psychosocial factors should be assessed to capture the complex reality of today's working world 21 .…”
Section: Discussionmentioning
confidence: 99%
“…There is always a trade‐off between the limitations of conceptual focus that are inherent to theoretical models and the desire to understand the full complexities of the real world 19 . Thus, the variety of possible psychosocial factors (some considered and others not considered in the models) that are present in the real psychosocial work environment should be measured to capture the complex reality of today's working world 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…Im Alltagsgebrauch ist "Stress" überwie-gend negativ belegt und mit Erscheinungen von leichter Gereiztheit bis zum Zustand chronischer Erschöpfung assoziiert. Nachweise für Ursache-Wirkungs-Ketten, die bei den Lebensumständen einer Person anfangen und über die Entwicklung von Stress-Symptomen bis zu Angststörungen, Depression oder Herz-Kreislauf-Erkrankungen führen, liegen vor, sind aber nur in aufwendigen Langzeitbeobachtungen zu entdecken [2,3]. Die Erweiterung des Arbeitsschutzgesetzes um den Hinweis, dass Arbeitgeber neben den physischen Arbeitsbedingungen die psychischen Belastungen ihrer Beschäftigten untersuchen müssen, gibt der Identifikation und Prävention von Stress bei der Arbeit und seinen Ursachen ein Fundament (ArbSchG § 5).…”
Section: Hintergrundunclassified